Surgical Treatment for Severe Scoliosis in Patients with Reduced Cardiorespiratory Function after Surgery for Congenital Heart Disease: A Report of Two Cases - Hayato Kinoshita; Naohisa Miyakoshi; Michio Hongo; Akiko Misawa; Daisuke Kudo; Yoichi Shimada (Case Reports in Orthopedics)
Purpose. Congenital heart disease (CHD) is associated with an increased risk of scoliosis. The prognosis of scoliosis patients with CHD has improved because of advances in cardiac care. As a result, the frequency of surgery for scoliosis in this population has increased, although the risk of perioperative complications remains high. We treated two patients with CHD who underwent surgery for severe scoliosis. To avoid perioperative complications, we evaluated the preoperative cardiac status and anesthetic risks before posterior correction and fixation in both patients. Methods. An expert anesthesiologist evaluated the anesthetic risk in each case, and an adequate reservoir of autologous blood was collected preoperatively. The patient in case 1 was at risk of significant blood loss and required extremely careful operative technique. The patient in case 2 had low cardiac output preoperatively. We therefore performed a thorough preoperative cardiac evaluation. Both patients were admitted to the intensive care unit postoperatively. Results. Neither patient suffered serious complications, and both achieved favorable outcomes. Conclusions. Appropriate surgical technique and teamwork among experts are the keys to success in patients with severe scoliosis and CHD.